Barking up the wrong tree? Use of polymerase chain reaction to diagnose syphilitic aortitis. Issue 10 (1st October 2002) - O'Regan, A W; Castro, C; Lukehart, S A; Kasznica, J M; Rice, P A; Joyce-Brady, M F
Abstract : The presentation of syphilitic aortitis is often atypical and available serological tests are non-specific. The diagnostic gold standard remains direct identification of microorganisms in tissue. We present a case of syphilitic aortitis that presented as a mediastinal mass and report the use of polymerase chain reaction for Treponema pallidum to diagnose syphilitic aortic disease.